Effects of miRNAs on myocardial apoptosis by modulating mitochondria related proteins. (April 2017) - Zhao, Yanfang; Ponnusamy, Murugavel; Dong, Yanhan; Zhang, Lei; Wang, Kun; Li, Peifeng
Summary: Myocardial apoptosis play a vital role in pathogenesis of cardiovascular diseases. The intrinsic pathway of apoptosis (mitochondrial apoptosis pathway) and abnormal mitochondrial fission and fusion have a detrimental effect on cells under a variety of intracellular stresses including hypoxia, oxidative stress, drug toxicity or DNA damage and contributes to the development of heart failure (HF), myocardial infarction (MI), diabetic cardiomyopathy and ischaemia/reperfusion injury (I/R). MicroRNAs (miRNAs) are endogenous short non‐coding RNAs, which target 3′‐untranslated region of mRNA to switch off gene expression. They play crucial roles in regulating complicated cardiac signalling and transcriptional events during cardiac development as well as in diseased condition. In this review, we summarize the molecular mechanism of mitochondrial apoptosis in cardiac cells and influence of miRNAs on them. MiRNAs regulate cardiac mitochondrial apoptosis by exert their effects on mitochondrial fission and fusion, reactive oxygen species (ROS) generation and Ca 2+ homeostasis, Bcl‐2 family members, and other mitochondrial function proteins. This advancement in understanding mechanism of cardiac cells death provides us new therapy targets for cardiovascular diseases associated with mitochondrial dysfunctions.